Analisis Minat Baca dan Dampaknya terhadap Pemahaman Bacaan Siswa Sekolah Dasar - Ramadhani, Cindy Dwi; Fadhilla Z., Ariska; Adrias, Adrias; Suciana, Fadila (DIDAKTIS : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Reading interest is a major factor in improving literacy, which plays an important role in students' reading comprehension. However, the low interest in reading in Indonesia is a major challenge that impacts on the quality of human resources and the development of education. This study aims to analyze the reading interest of SD Negeri 01 Pauh Sangik students and its impact on their reading comprehension. The method used is qualitative research with a case study approach, which involves observation, interviews and data analysis to understand the factors that influence students' reading interest. The results showed that students' reading interest is still relatively low, with a tendency to decrease from year to year. Students with high reading interest show better comprehension of the text, while students with low reading interest have difficulty in capturing the content of the text thoroughly. Some of the factors that contribute to low reading interest include internal factors, such as lack of personal motivation, as well as external factors, such as lack of parental support, lack of access to interesting books, and less interactive teaching methods. Therefore, strategies that involve schools, teachers and families in improving reading culture are needed, such as providing interesting reading materials, organizing literacy programs and implementing more innovative and interactive learning methods. Thus, this study is expected to be a reference in improving students' interest in reading from an early age in order to build strong and sustainable literacy in the future.